2016
DOI: 10.1074/jbc.m116.739664
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features and Functional Dependency on β-Clamp Define Distinct Subfamilies of Bacterial Mismatch Repair Endonuclease MutL

Abstract: In early reactions of DNA mismatch repair, MutS recognizes mismatched bases and activates MutL endonuclease to incise the error-containing strand of the duplex. DNA sliding clamp is responsible for directing the MutL-dependent nicking to the newly synthesized/error-containing strand. In Bacillus subtilis MutL, the ␤-clamp-interacting motif (␤ motif) of the C-terminal domain (CTD) is essential for both in vitro direct interaction with ␤-clamp and in vivo repair activity. A large cluster of negatively charged re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
(79 reference statements)
1
25
0
Order By: Relevance
“…This suggests that activation by millimolar Mn 2+ is the result of substitution for one or both endogenous zinc ions and that this effect can be reversed by low concentrations of exogenous Zn 2+ . The endonuclease motifs described above are found in many but not all bacterial MutL proteins ( 3 , 30 ), where they are also believed to comprise Zn 2+ binding endonuclease active sites that are subject to Mn 2+ activation ( 31 ). NMR analysis of the Aquifex aeolicus MutL CTD has shown that Mn 2+ binds in the proximity of the DQHA(X) 2 E(X) 4 E and CPHGRP zinc coordination motifs ( 32 ), which is consistent with our findings based on functional assays.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that activation by millimolar Mn 2+ is the result of substitution for one or both endogenous zinc ions and that this effect can be reversed by low concentrations of exogenous Zn 2+ . The endonuclease motifs described above are found in many but not all bacterial MutL proteins ( 3 , 30 ), where they are also believed to comprise Zn 2+ binding endonuclease active sites that are subject to Mn 2+ activation ( 31 ). NMR analysis of the Aquifex aeolicus MutL CTD has shown that Mn 2+ binds in the proximity of the DQHA(X) 2 E(X) 4 E and CPHGRP zinc coordination motifs ( 32 ), which is consistent with our findings based on functional assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported the crystal structure of the aqMutL CTD complexed with three cadmium ions . Here, in order to reveal the crystal structure with zinc ions, we incubated the aqMutL CTD in a buffer containing 0.5 m m zinc acetate, concentrated the protein, and created the crystal in the presence of 5 m m zinc ions.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc ions are shown as cyan spheres. (B) The crystal structure of the aqMutL CTD monomer with three cadmium ions ( PDB ID : 5B42) . Cadmium ions are shown as orange spheres.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations